Degradable photopolymerized thiol-based solid polymer electrolytes towards greener Li-ion batteries. (28th September 2015) - Chiappone, A.; Gerbaldi, C.; Roppolo, I.; Garino, N.; Bongiovanni, R.
Abstract: Thermoset initiator-free membranes are prepared by the UV-induced photopolymerization of thiol and (meth)acrylic monomers having polyethylene oxide chains, being known that the use of such monomers can lead to the formation of readily degradable membranes. The photopolymerization of different formulations is studied and the influence of the addition of a monofunctional methacrylate is investigated. By incorporation of lithium bis(oxalate)borate salt, solid polymer electrolytes are prepared and used as electrolyte membranes in Li-ion batteries. The ionic conductivity of the samples is measured and correlated to their thermal characteristics. The best performing sample shows encouraging cycling behaviour when tested in a truly-solid state lab-scale lithium test cell, thus enlightening the promising prospects of the newly designed polymer electrolytes. Furthermore, a preliminary degradation study is performed demonstrating the possibility to hydrolytically degrade the proposed UV cured networks making them extremely appealing for the development of sustainable and easily recyclable, thus greener, energy power sources. Graphical abstract: Highlights: UV-cured initiator-free membranes based on thiols and PEGacrylates monomers are prepared. By incorporating LiBOB solid polymer electrolytes for Li-ion batteries are prepared. Ionic conductivity is measured and related to thermal properties of the samples. The electrolyte shows encouraging cycling behaviour lab-scale lithium test cell. Ester groups near sulfides in the polymer allow fast degradation at high pH conditions.